Septic shock: Three years experience in an Intensive Treatment Center - Correa, Humberto; Artucio, Hernán; Caritat, Ricardo; González, Tabaré; Mazza, Norma; Muchada, Raúl; Panizza, Rodolfo; Wolyvovics, Mendel (Cirugía del Uruguay, 1976)
3 year experience at the I.C.U. of the Clinicas Hospital, Montevideo. The authors report the analysis of 31 patients admitted to the ICU of the Clinicas Hospital, Montevideo, due to Septic Shock, during a 36-month period, starting on August 1, 1971. Surgical cases were predominant, principally those having been submitted to emergency abdominal surgery (45.8 %), gynecology (22.5 %) or urology (12.9%). Non-surgical patients were 19.3 %. The authors describe th